SPATIO-TEMPORAL DYNAMICS OF VEGETATION AS A FACTOR OF DYNAMICS OF HARMFUL INSECTS’ POPULATION - Диченко, О. Ю. (Scientific Progress & Innovations, 2015)
The article presents data about the influence of vegetation dynamics on the number of harmful insects. It is established that vegetation dynamics during the previous and current years affects the rate of growth of pest populations in a present year compared to last year. Quantitatively this effect is estimated using regression analysis. For the qualitative assessment of the impact of vegetation dynamics on the number of pests of sugar beet dynamic maps of the following types are offered: Aphis fabae, Asproparthenis punctiventris, Cassida nebulosa, Cassida nobilis, Tanymecus palliates. This tool allows you to visualize the complex nature of the processes that determine the dynamics of insect populations, including harmful ones.